Atmospheric pressure plasma treatment induces abscisic acid production, reduces stomatal aperture and improves seedling growth in Arabidopsis thaliana. (4th April 2021) - Wang, J.; Cui, D.; Wang, L.; Du, M.; Yin, Y.; Ma, R.; Sun, H.; Jiao, Z.
Abstract: Cold atmospheric pressure plasmas (CAPPs) have been widely used for pre‐sowing treatment in agriculture to accelerate seed germination; however, information on their application to pre‐transplant seedlings is scarce. The roles of the phytohormone abscisic acid (ABA) on guard cell aperture that control air exchange with the environment were investigated after CAPPs treatment. In this study, Arabidopsis thaliana seedling growth was evaluated under CAPPs treatment at different doses. Besides, the optimal growth stimulation dose was selected to further evaluate changes in ABA, ROS, Ca 2+ and stomatal aperture during growth .The expression of most ABA signalling genes were aslo examined to investigate the mechanism. CAPPs treatment for 1 min significantly promoted Arabidopsis seedling growth; the ABA concentration in seedlings increased and peaked 48 h after treatment but was lower than in the control after 96 h. Transcript levels of most ABA signalling genes were markedly enhanced at 48 h, although their transcripts were significantly downregulated after 96 h. CAPPs treatment also reduced stomatal aperture after 24 h and accelerated ROS accumulation in guard cells. The Ca 2+ concentration in the treatment group was markedly higher than in the control at 24 and 96 h. The results suggest that CAPPs treatment accelerates ABA accumulation in Arabidopsis at early growth stages and ABA regulates ROS and Ca 2+ concentrations to affect stomatal aperture, and both ABA and stoma size are affected in CAPPs stimulation of Arabidopsis seedling growth. Abstract : CAPPs can stimulate Arabidopsis growth by adjusting abscisic acid accumulation and stoma size by regulating ROS/Ca 2+ concentration.